1) a(n) = n/(√n + 1)
a(1) = 1/(√1 + 1) = 1/2; a(2) = 2/(√2 + 1); a(3) = 3/(√3 + 1)
a(4) = 4/(√4 + 1) = 4/3; a(5) = 5/(√5 + 1)
2) a(n) = 2n/(√3n - 1)
a(1) = 2/(√3 - 1); a(2) = 4/(√6 - 1); a(3) = 6/(√9 - 1) = 6/(3 - 1) = 3
a(4) = 8/(√12 - 1); a(5) = 10/(√15 - 1)
3) a(n) = (2n - 1)/(√n + 2)
a(1) = 1/(√2 + 2); a(2) = 3/(√2 + 2); a(3) = 5/(√3 + 2)
a(4) = 7/(√4 + 2) = 7/4; a(5) = 9/(√5 + 2)
4) a(n) = 3n/(√(2n-1) + 1)
a(1) = 3/(√1 + 1) = 3/2; a(2) = 6/(√3 + 1); a(3) = 9/(√5 + 1)
a(4) = 12/(√7 + 1); a(5) = 15/(√9 - 1) = 15/2
Пошаговое объяснение:
Пусть кошки были α, β, A, и B.
α + β = 7
α + A = 8
α + B = 9
β + A = 10
β + B =11
B + A = 12
Сложим все эти уравнения:
α + β + α + A + α + B + β + A + β + B + B + A = 7 + 8 + 9 + 10 + 11 + 12
3 * α + 3 * β + 3 * A + 3 * B = 57
3 ( α + β + A + B ) = 57
( α + β + A + B ) = 57 / 3 = 19